Agro-Climatic Regional Planning An Overview - Planning Commission (Planning Commission, 1989)
The strategy of agro-climatic planning aims at a more scientific utilisation of available resources, both natural and manmade. The potential for growth and diversification would be fully exploited taking a holistic view of the climate, soil type, topography, water resources and irrigation facilities and relating them to requirements of output and employment. The concept of planning based on regional potential has a long term perspective and is being amplified and operationalised for the purpose. As a first step, the country has been divided into 15 Regions delineated on the basis of a commonality of agro-climatic factors like soil type, rainfall, temperature, water resources, etc. A farming system approach at the disaggregated level, rather than the traditional crop production approach, is being attempted.
Planning Commission Government of India
Planning Commission Government of India